Comment on 'Acne and nutrition: hypotheses, myths and facts'. (9th July 2019) - Donnarumma, M.; Savastano, S.; Barrea, L.; Blasio, C.; Colao, A.; Fabbrocini, G.
Abstract : Linked article: J.P. Claudel. J Eur Acad Dermatol Venereol 2019; 33 : e420. https://doi.org/10.1111/jdv.15722 .